2022
DOI: 10.1155/2022/4933255
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Astragali Radix Extract Injection Combined with Bone Marrow Mesenchymal Stem Cells in Bleomycin-Induced Pulmonary Fibrotic Rats

Abstract: Pulmonary fibrosis is a serious disease for which effective drugs are unavailable. Here, we treated rat models of bleomycin (BLM)-induced pulmonary fibrosis with Astragali Radix extract injection (AI) combined with or without bone marrow mesenchymal stem cells (BMSCs). We injected rats intratracheally with BLM and transplanted BMSCs via tail vein injection 15 days later. We also intraperitoneally injected AI daily from days 15 to 28. Changes in lung pathology and function, as well as the levels of matrix metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A recent study demonstrated the protective effect of BYHWD on a pulmonary fibrosis model in vitro, with its mechanism related to the inhibition of pulmonary inflammation, collagen deposition, and EMT by suppressing the TGF-β1 signaling pathway 37 . An AM extract injection has been reported to ameliorate pathological lung fibrotic damage caused by bleomycin in rats and improve lung function by reducing the expression levels of TGF-β1 and collagens I and III, while increasing those of MMP-3 , MMP-9 , TIMP-1 , CXCL12 , and CD90 38 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated the protective effect of BYHWD on a pulmonary fibrosis model in vitro, with its mechanism related to the inhibition of pulmonary inflammation, collagen deposition, and EMT by suppressing the TGF-β1 signaling pathway 37 . An AM extract injection has been reported to ameliorate pathological lung fibrotic damage caused by bleomycin in rats and improve lung function by reducing the expression levels of TGF-β1 and collagens I and III, while increasing those of MMP-3 , MMP-9 , TIMP-1 , CXCL12 , and CD90 38 .…”
Section: Discussionmentioning
confidence: 99%
“…33 AM extract injection has been reported to ameliorate pathological lung brotic damage caused by BLM in rats and improve lung function by reducing the expression levels of TGF-β1 and collagens I and III whereas elevating those of MMP-3, MMP-9, TIMP-1, CXCL12, and CD90. 34 Therefore, we used network pharmacology analysis to investigate the common transcription factor regulatory network in IPF and identi ed AM and RPR as candidate drugs for IPF. The therapeutic effect and mechanism of AM and RPR were veri ed in vivo, and the network pharmacology analysis revealed their molecular functions and pharmacological targets for treating IPF.…”
Section: Discussionmentioning
confidence: 99%